A Sense of Obligation: Cultural Differences in the Experience of Obligation. (November 2018) - Buchtel, Emma E.; Ng, Leo C. Y.; Norenzayan, Ara; Heine, Steven J.; Biesanz, Jeremy C.; Chen, Sylvia Xiaohua; Bond, Michael Harris; Peng, Qin; Su, Yanjie
In this investigation of cultural differences in the experience of obligation, we distinguish between Confucian Role Ethics versus Relative Autonomy lay theories of motivation and illustrate them with data showing relevant cultural differences in both social judgments and intrapersonal experience. First, when judging others, Western European heritage culture (WEHC) participants (relative to Confucian heritage culture [CHC] participants) judged obligation-motivated actors more negatively than those motivated by agency (Study 1, N = 529). Second, in daily diary and situation sampling studies, CHC participants (relative to WEHC participants) perceived more congruency between their own agentic and obligated motivations, and more positive emotional associations with obligated motivations (Study 2, N = 200 and Study 3, N = 244). Agentic motivation, however, was universally associated with positive emotions. More research on a Role Ethics rather than Relative Autonomy conception of agency may improve our understanding of human motivation, especially across cultures.